Synthesis and Electrochemical Properties of a Novel Mono-meso-ferrocenyl Porphyrin - Niemevz, Fernando (2006)
A synthetic route to mono-meso-ferrocenyl porphyrins using a MacDonald-type 2+2 condensation is described. In this method, the substituted diformyldipyrrylmethane 4 is treated with the dicarboxydipyrrylmethane 6. The 5-ferrocenyldipyrrylmethane was obtained by condensation of benzyl 3-methyl-4-ethylpyrrol-2-carboxylate with ferrocenecarboxaldehyde in the presence of p-toluenesulfonic acid. The unequivocal assignment of all proton resonances in the new porphyrin was achieved by means of a detailed analysis of its H-H NOESY correlations. Interestingly, we noticed that the ferrocenyl group introduces an element of asymmetry in the molecule. The corresponding Co(II) and Ni(II) complexes were also prepared. In cyclic voltammograms of the free base and the Co or Ni complexes all voltammetric peaks disappear after four consecutive scans. This result suggests no film formation in any of them.